Non-toxic perfringolysin O and α-toxin derivatives as potential vaccine candidates against bovine necrohaemorrhagic enteritis. (November 2016) - Verherstraeten, S.; Goossens, E.; Valgaeren, B.; Pardon, B.; Timbermont, L.; Haesebrouck, F.; Ducatelle, R.; Deprez, P.; Van Immerseel, F.
Highlights: Bovine necrohaemorrhagic enteritis. Perfringolysin derivative PFOL491D is a safe, non-toxic, immunogenic antigen. Antisera inhibited the perfringolysin-associated haemolytic activity. Antisera had neutralizing capacity against the Clostridium perfringens cytotoxic effect. α-toxin derivative GST-cpa247-370 has an added neutralizing effect on cytotoxicity. Abstract: Bovine necrohaemorrhagic enteritis is a fatal Clostridium perfringens type A-induced disease that is characterised by sudden death. Recently the involvement of perfringolysin O and α-toxin in the development of necrohaemorrhagic lesions in the gut of calves was suggested, and thus derivatives of these toxins are potentially suitable as vaccine antigens. In the current study, the perfringolysin O derivative PFO L491D, alone or in combination with α-toxin derivative GST-cpa247-370, was evaluated as possible vaccine candidate, using in vitro assays. PFO L491D showed no haemolytic effect on horse red blood cells and no cytotoxic effect on bovine endothelial cells. Furthermore, calves immunised with PFO L491D raised antibodies against perfringolysin O that could inhibit the perfringolysin O-associated haemolytic activity on horse red blood cells. Antisera from calves immunised with PFO L491D had a significantly higher neutralising capacity against the cytotoxic effect of C. perfringens culture supernatant to bovine endothelial cells than serum from control calves ( P < 0.05). Immunisation of calves with PFO L491D in combination with GST-cpa247-370 elicited antibodies against perfringolysin O and α-toxin and consequently inhibited both the perfringolysin O-associated haemolytic activity and the α-toxin-associated lecithinase activity in vitro. Additionally, the neutralising ability of these antisera on the cytotoxic effect of C. perfringens culture supernatant to bovine endothelial cells was significantly higher than that from calves immunised with PFO L491D ( P < 0.001). In conclusion, perfringolysin O derivative PFO L491D is an immunogenic antigen that can potentially be used to produce vaccine against bovine necrohaemorrhagic enteritis. Including α-toxin derivative GST-cpa247-370 has an additional protective effect and therefore vaccination of calves with a combination of both antigens seems even more promising.